Design and Development of a Research Integrated Geoinformation System with a Fuzzy Expert System - Burnashev, Rustam A.; Khairullin, Bulat M.; Prokopyev, Nikolai A.; Farahov, Rustam A.; Bolsunovskaya, Marina V.; Enikeev, Arslan I. (2023 IEEE 24th International Conference of Young Professionals in Electron Devices and Materials (EDM), 2023)
The paper presents a software toolkit that includes components of a fuzzy expert system and a geographic information system. Fuzzy expert system methods were applied to improve the decision-making efficiency when working with incomplete and inconsistent data. Geographic information technologies were used to distribute and visualize spatial data on the map. The interaction of both components will increase the efficiency of scientific projects in solving various tasks in research processes. Access to the knowledge base replenishment and processing is carried out by a subject-matter expert (administrator), while a common user has an access to elements of an intelligent fuzzy search and a visualizer (map). The software tool is a web resource capable of functioning on all modern platforms. Our research is aimed at improving the efficiency of decision-making in challenging circumstances.